Pengaruh Inovasi Destinasi Wisata Berbasis E-Government dan Partisipasi Masyarakat terhadap Pembangunan Berkelanjutan di Pulau Lusi - Sukmana, Hendra (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
In practice, sustainable development is still needed on Lusi Island considering that the existence of Lusi Island is not yet known by the wider community and the development plan has not been realized in the form of adding several tourist and educational facilities. The purpose of this study is to determine and analyze the influence of e-government-based tourist destination innovation and community participation both partially and simultaneously on sustainable development in the field of Lusi Island tourism. Data analysis was performed by multiple linear regression analysis. The results showed that there was a partial and simultaneous influence of e-government-based tourist destination innovation and community participation in sustainable development in the field of Lusi Island tourism. Sidoarjo Regency is expected to maximize the development and promotion of Lusi Island tourism, for example by implementing online ticket purchases and promotions through official social media.